Scapular upward-rotation deficits after acute fatigue in tennis players - Rich, R. L.; Struminger, A. H.; Tucker, W. S.; Munkasy, B. A.; Joyner, A. B.; Buckley, T. A. (Journal of Athletic Training, 2016)
Context: Fatigue in overhead athletes reduces shoulder muscular contraction and proprioception. These deficits may lead to alterations in scapular upward rotation, which is associated with multiple chronic shoulder conditions prevalent in tennis players.